2017
DOI: 10.1186/s12903-017-0368-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric characteristics of the “General Oral Health Assessment Index (GOHAI) » in a French representative sample of patients with schizophrenia

Abstract: BackgroundThe “General Oral Health Assessment Index” (GOHAI) was widely used in clinical or epidemiological studies worldwide, as it was available for use in different languages. Therefore, the aim of this study was to evaluate the psychometric characteristics of the GOHAI in a representative sample of patients with schizophrenia.MethodsA total of 90 schizophrenic patients (in-patients and out-patients) were recruited from the participants of the “buccodor study” (NCT02167724) between March and September 2015.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 52 publications
(76 reference statements)
0
37
1
1
Order By: Relevance
“…It also has been used in a cohort of adults with a chronic disease . A recent study validated the French translation of the GOHAI in a population of adults with a mental pathology (mean age 47 years) . We did not have a control group without diabetes, because our aim was not to compare people with and without diabetes but rather to work on people with diabetes and to compare them both by status (T1DM/T2DM) and according to glycaemic balance.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been used in a cohort of adults with a chronic disease . A recent study validated the French translation of the GOHAI in a population of adults with a mental pathology (mean age 47 years) . We did not have a control group without diabetes, because our aim was not to compare people with and without diabetes but rather to work on people with diabetes and to compare them both by status (T1DM/T2DM) and according to glycaemic balance.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the correlations between the OHRQoL and oral clinical status among elderly individuals with mild dementia were weaker than those among elderly individuals with normal cognitive function. However, some studies that investigated the OHRQoL among psychiatric patients and used the GOHAI questionnaire with similar exclusion criteria reported that the reliability of the questionnaire was good [25,26]. Third, this study was a cross-sectional study.…”
Section: Discussionmentioning
confidence: 93%
“…The mean±SD of the GOHAI score was 49.7±7.9 in this study. A previous study in France reported that the mean±SD of the GOHAI score was 45.5±8.4 among schizophrenic patients and that the GOHAI score was lower than that of the general population [26]. A previous study in Japan reported that the mean GOHAI scores among general Japanese adults (20-69 years) ranged from 51.3 to 54.8 [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations